Dampak pergeseran sosial pasca – Industrialisasi - Aditya Arifin; Purwanti, Purwanti (GLOBAL SCIENTS PUBLISHER, 2025)
This journal explores the impact of industrialization on the social structure and local culture in Jayamukti Village, Cikarang. Utilizing qualitative methods, including interviews, observations, and focus group discussions, the research reveals that industrialization has transformed the community's livelihoods from traditional agriculture to industrial employment. This shift has led to a significant population increase, from approximately 230,000-250,000 before 1990 to around 550,000 in 2023. The emergence of a new social class has created notable disparities between long-term residents, primarily traditional farmers and small business owners, and new migrants working in the industry. While some residents perceive enhanced economic opportunities, others feel that industrialization has not substantially benefited local income. Environmental issues related to inadequate industrial waste management have also been identified, negatively affecting local water sources. The journal recommends skill enhancement programs through training and government support for cultural preservation and social activities to bridge existing social gaps. These findings highlight the challenges and opportunities faced by the community in adapting to the changes brought about by industrialization